GaYme Changers in Slovakia: The Slovak LGBT+ community and their allies: a challenging climate, a murderous attack and some progress in companies and civil society - Schadendorf, Jens (LID Publishing, 2023)
GLOBAL LGBT+ EQUALITY – SLOVAKIA'S STORY In his groundbreaking book GaYme Changer: How the LGBT+ community and their allies are changing the global community, Jens Schadendorf described a revolution: in less than a decade, gay, lesbian, transgender, bisexual, and queer people in the West and some other parts of the world broke free from their long history of marginalization, stigmatization, and criminalization to become the ultimate champions of creativity, diversity, and innovation. Now, in this shorter work, Schadendorf looks at Slovakia, where LGBT+ people and their supporters face political and religious attitudes that can fuel hate speech, discrimination, and even, recently, murderous violence. But there is also hope, with campaigning organizations, individuals, and companies bravely leading the way. Even in the face of hostility, what applies elsewhere in the world applies here too: letting LGBT+ people develop into dynamic forces is a benefit to both business and society. It is economically right, and it is socially and ethically the right thing to do. "…GaYme Changer is a must-read in these times of growing uncertainty and polarization. I am thrilled that in GaYme Changers in Slovakia, we can now read new, comprehensive, and insightful backgrounds and stories on my country."Matej Ftá?nik, Co-Founder and CEO, Vacuumlabs, Bratislava Praise for GaYme Changer "The LGBT+ community has made great strides in the global business arena in recent years … Yet, this progress is not universal. The world needs more GaYme Changers. This book is an inspirational call-to-action to make this happen."Sander van 't Noordende, CEO, Randstad "… a must-read for anyone seeking to drive and establish positive change."Natalia Oropeza, Chief Diversity Officer, Siemens "Global developments and new role models, corporate social responsibility, and the economic benefits of LGBT+ diversity and inclusion – all in one … a must-read!"Professor Christoph Lu?tge, Chair of Business Ethics, Technical University of Munich "… Jens Schadendorf's book is an insightful and compelling read – essential for every leader and those driving inclusion at all levels."Antonio Zappulla, CEO, Thomson Reuters Foundation, London